A Textual Analysis of the Use of Sunna in Malik's Legal Doctrine - Kusmana Kusmana (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2000)
This paper explores Malik's use of the sunna as a crucial source in his legal doctrine, highlighting its significance in the development of Islamic jurisprudence. While Malik's legal thought draws from various sources, including the Qur'an and customary law, the focus of this study is on his methodology in applying the sunna. Recognized for his early contributions to Islamic legal theory, Malik's work, particularly his Muwatta', is frequently cited, underscoring the impact of the sunna in his legal opinions. The paper will examine Malik's references to the sunna, assess its role in his legal reasoning, and consider how the concept of sunna was understood before and during his lifetime.